2021
DOI: 10.1177/1071181321651293
|View full text |Cite
|
Sign up to set email alerts
|

Learning Affordances: Theoretical Considerations for Design of Immersive Virtual Reality in Training and Education

Abstract: Technological advances have led to a rapid increase in the implementation of virtual reality (VR) across multiple sectors of society. Further, we are seeing more researchers explore how the technology can be used to promote learning and training in a variety of domains. But there is a problematic gap between development of VR for training and education and learning theory to ensure its efficacy. We address this need by providing a theoretical lens through which to evaluate existing research in VR. We consider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Beyond priming affordances of custom and personalized VR environments (Shin, 2017;McGowin et al, 2021), characters and avatars offer further advantages. Avatar embodiment techniques that offer participants the opportunity to inhabit custom personas of other races or cultures show great promise in reducing stereotypes, low self-perception, and negative academic performance associated with stereotype threats (Peck et al, 2013).…”
Section: Figure 8 Vret Fear Extinction Cyclementioning
confidence: 99%
“…Beyond priming affordances of custom and personalized VR environments (Shin, 2017;McGowin et al, 2021), characters and avatars offer further advantages. Avatar embodiment techniques that offer participants the opportunity to inhabit custom personas of other races or cultures show great promise in reducing stereotypes, low self-perception, and negative academic performance associated with stereotype threats (Peck et al, 2013).…”
Section: Figure 8 Vret Fear Extinction Cyclementioning
confidence: 99%
“…Yet, the study of Work Design and Ergonomics Laboratory indicated a difference between the hands-on in-person lab and remote lab. Hands-on labs provide students with realistic scenarios that could occur in the industry: debugging technological errors, teamwork communication, setting up physical equipment (McGowin et al, 2021). The paper debates that simulated labs achieve more professional skills and conceptual understanding.…”
Section: Introductionmentioning
confidence: 99%
“…However, the institution made computer labs available during the pandemic for ensuring student access to the internet, and the instructor provided recordings of the lab sessions. Although AR/VR systems allow the learner to interact with team members and do hands-on lab tasks virtually for human factors, those systems require expensive set-ups in cost, knowledge, time, and customization to teach the exact concept at hand (McGowin et al, 2021). As a result, the incorporation of AR/VR in the Work Design and Ergonomics Laboratory could not be completed in Fall 2020 quickly.…”
Section: Introductionmentioning
confidence: 99%